2010
DOI: 10.1038/cr.2010.35
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctionality of the linker histones: an emerging role for protein-protein interactions

Abstract: Linker histones, e.g., H1, are best known for their ability to bind to nucleosomes and stabilize both nucleosome structure and condensed higher-order chromatin structures. However, over the years many investigators have reported specific interactions between linker histones and proteins involved in important cellular processes. The purpose of this review is to highlight evidence indicating an important alternative mode of action for H1, namely protein-protein interactions. We first review key aspects of the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 123 publications
(119 reference statements)
2
67
0
2
Order By: Relevance
“…The histone H1 CTD has been implicated in chromatin condensation, and recent in vitro studies indicate this property localizes to two subdomains (37). Histone H1 has been reported to bind a number of other proteins, but in many cases the binding regions and functional consequences of binding have not been explored (31). However, two examples of functionally important interactions between the histone H1 CTD and other proteins have been studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The histone H1 CTD has been implicated in chromatin condensation, and recent in vitro studies indicate this property localizes to two subdomains (37). Histone H1 has been reported to bind a number of other proteins, but in many cases the binding regions and functional consequences of binding have not been explored (31). However, two examples of functionally important interactions between the histone H1 CTD and other proteins have been studied.…”
Section: Discussionmentioning
confidence: 99%
“…H1 linker histones consist of three domains, a short N-terminal region, a central, highly structured globular region, and a basic Cterminal domain (CTD) (31). To determine which of these regions interact with DNMTs, we prepared three fusion proteins in which GST was joined to full-length H1d or to the first 151 or the last 70 residues of H1d.…”
Section: Resultsmentioning
confidence: 99%
“…However, in vivo H1 has been shown to be more dynamic than core histones (Lever et al 2000;Misteli et al 2000). Several knockout studies across a wide range of organisms revealed that H1 has multiple functions, including participation in the regulation of most nuclear processes (Izzo et al 2008;Happel and Doenecke 2009), mediated at least in some cases by specific H1-protein interactions (McBryant et al 2010). H1 depletion leads to perturbation in the expression of only a subset of genes, with both up-regulation and down-regulation (Shen and Gorovsky 1996;Hellauer et al 2001;Fan et al 2005).…”
mentioning
confidence: 99%
“…As a consequence, histone H1 is engaged in a range of activities, including cell cycle regulation and cellular response as well as repair of damaged DNA and transmission of the apoptotic signals (Roque et al, 2016). Moreover, the scope of histone H1 activity is broader due to its interactions with varied proteins of both nuclear (McBryant et al, 2010) and nucleolar (Kalashnikova et al, 2016) localization.…”
Section: Introductionmentioning
confidence: 99%